Hydrogenative Catalysis with Three‐Coordinate Zinc Complexes Supported with PN Ligands is Enhanced Compared to PNP Analogs. Issue 40 (31st May 2022) - Paul, Sanchita; Morgante, Pierpaolo; MacMillan, Samantha N.; Autschbach, Jochen; Lacy, David C.
Abstract: This work details the synthesis, characterization, and catalytic activity of reactive low‐coordinate organozinc complexes. The complexes activate hydrogen and they appear to be more active in hydrogenation of ketones and imines than their tridentate pincer analogs. This is thought, in part, to be due to the lack of trailing third phosphorus arm present in previous work. DFT computations reveal a sigma‐bond metathesis mechanism is comparable to an alternative aromatization/dearomatization metal‐ligand cooperative mechanism. Abstract : Catalytic activity of bidentate three‐coordinate Zn(II) complexes towards hydrogenation of model ketone and imine substrates is enhanced compared to the analogous tridentate PNP system. DFT calculations and experimental evidence point towards a sigma bond metathesis mechanism, instead of aromatization/dearomatization metal‐ligand cooperativity, with the lack of trailing P‐arm enabling the enhancement.